Question
(1). Simplify \( \left(\frac{2}{3}\right. \) of \( \left.\frac{3}{4}\right)+\frac{1}{2} \)
Ask by Wells Gibbs. in South Africa
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
The simplified result is 1.
Solution
To simplify the expression:
\[
\left(\frac{2}{3}\right) \text{ of } \left(\frac{3}{4}\right) + \frac{1}{2}
\]
**Step 1: Interpret "of" as multiplication**
In mathematical terms, "of" typically means multiplication. So, the expression becomes:
\[
\left(\frac{2}{3}\right) \times \left(\frac{3}{4}\right) + \frac{1}{2}
\]
**Step 2: Multiply the fractions**
\[
\frac{2}{3} \times \frac{3}{4} = \frac{2 \times 3}{3 \times 4} = \frac{6}{12} = \frac{1}{2}
\]
**Step 3: Add the remaining fraction**
\[
\frac{1}{2} + \frac{1}{2} = \frac{2}{2} = 1
\]
**Final Answer:**
\[
1
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Beyond the Answer
To simplify \( \left(\frac{2}{3}\right) \text{ of } \left(\frac{3}{4}\right) + \frac{1}{2} \), first calculate \( \frac{2}{3} \) of \( \frac{3}{4} \): \[ \frac{2}{3} \times \frac{3}{4} = \frac{2 \times 3}{3 \times 4} = \frac{6}{12} = \frac{1}{2} \] Now add \( \frac{1}{2} \): \[ \frac{1}{2} + \frac{1}{2} = 1 \] Thus, the simplified expression is \( 1 \).